An on-chip integrated current sensor with high precision and large current range for smart power ICs. (April 2023) - Xia, Ruirui; Cai, Xiaowu; Ding, Liqiang; Gao, Mali; Gao, Yuexin; Han, Tian; Dang, Jianying; Li, Bo
Abstract: This work presents a precision current sensor with a high gain amplifier. Three aspects are improved. Firstly, the gain boosting is achieved by adding nested-amplifiers, namely AMPH and AMPL . Secondly, the DC error is eliminated by implementing a cascode current mirror branch with bias current compensation. Thirdly, the damage of large negative overshoot voltage to the operational amplifier is avoided because of the inserted switch transistors disconnecting the amplifier from load. For the ratio of main-FET to sense-FET, a factor of M = 5000 is chosen to keep the power consumption low. Measurement results show that this current sensor can operate from −60 °C to 120 °C with supply voltage from 10 V to 30 V. The measured absolute error between the sensed signal and the load current is less than 3% in range of 20 mA to 3.6 A at 27 °C . This current sensor has been fabricated in a 0.5 μ m SOI BCD process, which can be applied in smart power ICs.